BUILDING FOUNDATIONS FOR LITERACY: LEARN TO READ, READ TO LEARN PROGRAM (Lex localis - Journal of Local Self-Government, 2025)
This study presents an overview of the Learn to Read, Read to Learn program, implemented at Gulod Elementary School in Cabuyao, Laguna, in the Alpabasa program. The initiative aims to improve early literacy by equipping teachers with effective reading instruction strategies and providing Kindergarten students with interactive workbooks to enhance their foundational skills. The program targeted 30 teachers from Kindergarten to Grade 3, who underwent intensive training in the Alpabasa methodology, which integrates phonics, listening skills, and engaging activities to improve reading comprehension. Additionally, over 100 Kindergarten pupils received workbooks designed to foster a love for reading. The training sessions, conducted over two days in March 2024, were followed by continuous monitoring and support to ensure the effective implementation of the teaching strategies. The expected outcomes include improved reading proficiency among students and a sustainable impact on literacy instruction at the school. The program aligns with the Department of Education’s goals of enhancing literacy and providing quality education, focusing on early childhood development. Through teacher empowerment and resource provision, the program aims to create a lasting change in the educational landscape, ensuring that students not only learn to read but also read to learn. The collaborative effort between various stakeholders is seen as a vital step toward improving the educational opportunities of Filipino children and building a future where every child is a confident reader.